Dampak Work Family Conflict dan Kepuasan Kerja terhadap Kinerja Pegawai: Studi pada Pegawai Negeri Sipil di Kantor Kementrian Agama Kabupaten Badung - Dewi, Ida Ayu Sri Purnama; Wijaya, Putu Yudy; Wulandari, Ni Luh Adisti Abiyoga (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2021)
To achieve organizational goals can be realize with human resources by improving employee performance. Performance can influenced by work family conflicts and job satisfaction that experienced by employees during work. This research was conducted at the Office of the Ministry of Religion, Badung Regency. The number of samples taken is 136 employees who are married with a non-probability sampling method which uses a saturation sampling technique. The data analysis techniques used were validity test, reliability test, path analysis and sobel test. Based on the analysis results obtained: (1) work family conflict has a significant effect on job satisfaction, with a tcount of -6.362 and a significance of 0.000 so H1 is accepted. (2) work family conflict has a significant effect on performance, with a tcount of -5.788 and a significance of 0.000 so H2 is accepted. (3) job satisfaction has a significant effect on performance, with a tcount of 6.611 and a significance of 0.000 so H3 is accepted. (4) work family conflict indirectly with performance through job satisfaction, with a zcount of 4.617 so H4 is accepted.